1983
DOI: 10.1002/apmc.1983.051160113
|View full text |Cite
|
Sign up to set email alerts
|

Electro osmosis in the system ion‐exchange membrane — sulphuric acid solution

Abstract: Electro osmotic phenomena in NAFION-120 or MRF-26 sulfonic acid membrane bisecting the same H,SO, solution were investigated. It was found that the transference numbers of hydrogen ions, tH in the NAFION membrane remain nearly constant and close to one even at a concentration of 1.8 mol/kg H,O of the external H,SO, solution, and in MRF-26 membranewhen the concentration reaches 1.5 mol/kg H,O. The transport numbers of water and consequently the volume electro osmotic flow in NAFION membrane change with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Our theory of autodissociative double layers began as an attempt of explaining the catalytic interaction between solid acid catalysts and solid cellulose, and it successfully explained a number of previously known experimental facts . The theory keeps gaining supportive evidence: In the present paper it is shown that generation of negative charge on pore walls of a sulfonic ionomer membranes due to dissociation of the acid groups can adequately (even semi‐quantitatively) explain both high cation selectivity of sulfonic ionomer membranes, and decline of this selectivity at high concentration of a strong acid background solution …”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Our theory of autodissociative double layers began as an attempt of explaining the catalytic interaction between solid acid catalysts and solid cellulose, and it successfully explained a number of previously known experimental facts . The theory keeps gaining supportive evidence: In the present paper it is shown that generation of negative charge on pore walls of a sulfonic ionomer membranes due to dissociation of the acid groups can adequately (even semi‐quantitatively) explain both high cation selectivity of sulfonic ionomer membranes, and decline of this selectivity at high concentration of a strong acid background solution …”
Section: Resultssupporting
confidence: 54%
“…Coincidentally, the predicted proton concentration at the strongly acidic pore wall in thin pores is 3–4 M (Figure a, pore radius 1 nm, pK 1) is comparable to the concentration of H 2 SO 4 in solution (2 M) at which this proton selectivity decrease occurs in Nafion, which is similarly narrow‐pored . Proton selectivity in MRF‐26 begins deteriorating at a lower H 2 SO 4 concentration (1.5 M).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations